2022
DOI: 10.1093/gerona/glac115
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Associations Between Adiposity and Cognitive Function: A Prospective Analysis of the Canadian Longitudinal Study on Aging (CLSA)

Abstract: Objectives Theoretical perspectives suggest that adiposity and cognitive function may be bidirectionally associated, but this has not been examined in a large-scale dataset. The current investigation aims to fill this gap using a large, representative sample of middle-aged and older adults. Methods Using data from the Canadian Longitudinal Study on Aging (CLSA; n = 25,854), the bidirectional hypothesis was examined with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…For example, it has been reported that children and adolescents with relatively weaker executive control, poorer planning, and more impulsivity at baseline were more likely to have high BMI at follow-up . The hypothesized bidirectional association between adiposity and cognitive function has also been reported in previous studies using adult samples . A recent meta-analysis of longitudinal studies involving children and adolescent samples showed that the existing literature supports a bidirectional relationship between adiposity and executive function .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…For example, it has been reported that children and adolescents with relatively weaker executive control, poorer planning, and more impulsivity at baseline were more likely to have high BMI at follow-up . The hypothesized bidirectional association between adiposity and cognitive function has also been reported in previous studies using adult samples . A recent meta-analysis of longitudinal studies involving children and adolescent samples showed that the existing literature supports a bidirectional relationship between adiposity and executive function .…”
Section: Discussionmentioning
confidence: 73%
“…[36][37][38][39] The hypothesized bidirectional association adiposity and cognitive function has also been reported in previous studies using adult samples. 7 A recent meta-analysis of longitudinal studies involving children and adolescent samples showed that the existing literature supports a bidirectional relationship between adiposity and executive function. 11 However, it should be noted that meta-analyses included studies that assessed adiposity to executive function or executive function to adiposity associations primarily with a unidirectional assumption, mostly in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The opposite relationship was also found whereby weight status was associated with poorer executive function, particularly working memory [69]. Bidirectional associations between obesity and cognition have also been reported in a large cohort of adults from the Canadian Longitudinal Study on Ageing [70]. Higher baseline waist circumference was associated with lower executive function at 3-year follow-up for middle aged adults and lower baseline executive function predicted higher waist circumference at follow-up.…”
Section: Longitudinal Associations Between Higher Cognitive Functions...mentioning
confidence: 99%